2010
DOI: 10.3748/wjg.v16.i5.531
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs, development of Barrett’s esophagus, and progression to esophageal adenocarcinoma

Abstract: Barrett's esophagus is a premalignant condition caused by gastroesophageal reflux. Once developed, it can progress through varying grades of dysplasia to esophageal adenocarcinoma. Whilst it is well accepted that Barrett's esophagus is caused by gastroesophageal reflux, the molecular mechanisms of its pathogenesis and progression to cancer remain unclear. MicroRNAs (miRNAs) are short segments of RNA that have been shown to control the expression of many human genes. They have been implicated in most cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Increasing evidences suggest that miRNAs play critical roles in many key biological processes, such as cell growth, tissue differentiation, cell proliferation, embryonic development, and apoptosis. Several recent studies have documented the role of miR-21, miR-143, miR-145, miR-194, miR-203, miR-205 and miR-215 in BE and EAC [47][48][49][50][51][52][53][54] (Table 1). However, there is lack of studies on the role of miRNAs in the pathogenesis of GERD.…”
Section: Mirnas In Be and Eacmentioning
confidence: 94%
“…Increasing evidences suggest that miRNAs play critical roles in many key biological processes, such as cell growth, tissue differentiation, cell proliferation, embryonic development, and apoptosis. Several recent studies have documented the role of miR-21, miR-143, miR-145, miR-194, miR-203, miR-205 and miR-215 in BE and EAC [47][48][49][50][51][52][53][54] (Table 1). However, there is lack of studies on the role of miRNAs in the pathogenesis of GERD.…”
Section: Mirnas In Be and Eacmentioning
confidence: 94%
“…Detection of IM in the distal esophagus as well as within the gastric cardia has been reported with an increasing frequency [15,16] . It was reported that the prevalence of BE and CIM is 2%-12% and 5%-23%, respectively, in patients undergoing routine upper gastrointestinal endoscopy [20,21] . Detection of IM in BE patients potentially commits the patients to regular surveillance endoscopy with biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal adenocarcinoma is a highly lethal tumour usually developing in the lower third of the esophagus, or at the gastro-esophageal junction[21]. Incidence rates have risen gradually in developed countries since 1984, with a 4% increase in the incidence of adenocarcinoma in Australia between 1988 and 2005[22].…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%